GLASS CEILING: SEBUAH STUDI LITERATUR - Muslim, Muhamad Ihwanul; Perdhana, Mirwan Surya (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
Nowadays, women's involvement in the workforce are continues to increase. However, the number of womens participate in the upper management are still limited. Such condition might be caused by glass ceiling phenomenon – obstacles hindering women’s career advancement. This study presents antecedents of glass ceiling phenomenon both in profit and non-profit organizations. Extensive literature review were conducted to gain conclusion on factors hindering women’s career advancement. Managerial implication and opportunity for further research were discussed.